Protagonism in childhood: participation in the daily lives of children with developmental delay - Souza Martins, Danyelle (2022)
This research discusses the prontagonism as an involvement in daily activities of children with child-development delay. It's main objective is to research about  protagonism and participation of children with child-development delay to understand how the child-caretaker relation establishes itself on a daily basis and to investigate what the possible obstacles are for the participation of children in daily activities. This study has a qualitative feature and was made using methods such as the semistructured interview, which was used with 9 caretakers of children treated  by professionals of the  the Rehabilitation Specialized Center II of Taguatinga-DF. It was verified that the caretakers demontrated in majority commitment to make participation as an oportunity  and to recognize the children as the  leading roles on daily activities. However,  issues related to developmental delay were identified as barriers to children's performance and involvement in daily activities such as communication, emotional aspects and social interaction.